Legal Consequences of Authentic Deed with False Identity Against Notary - Moses Nathanael; Benny Djaja; Maman Sudirman (Dinasti Research, 2024)
Given the very important role of Notaries in upholding justice and truth in society, everyone who participates in law enforcement is obliged to carry out their duties with integrity and devotion, thus raising the degree of the Notary profession to a noble level (officium nobile). This can lead to increasingly complex and challenging tasks amidst the increasingly intense competition between Notaries, which in turn causes some Notaries to be less careful in carrying out their official obligations. The rapid changes in society are accompanied by the increasing need for Notary services, especially in the midst of globalization. People need Notary services in order to carry out their legal obligations, especially in the framework of civil law, where the implementation of a legal action depends on the existence of supporting documents such as letters or documents. This deed is often made by a Notary in the form of an original deed, so that it has more legal weight because of its official and legal existence. Notaries are public officials who have the authority to make Deeds and other legal authorities, as stated in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Offices. In Indonesia, the legal system is very important to resolve various disputes between the government and the community. Another indication that legal certainty has been guaranteed is the stipulation or legalization of a contract by a Notary. The purpose of this normative legal research is to examine laws and regulations relating to the position and duties of Notaries in society